Pelatihan Masakan Thailand Berbasis Bahan Lokal untuk UMKM Kuliner di Kecamatan Deli Serdang sebagai Strategi Diversifikasi Produk Ekonomi Kreatif - Shara, Yuni; Akmal, Oktafiana; Ongah, Harun; Syahrizal, Muhammad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This community service program aims to enhance the capacity of micro, small, and medium enterprises (MSMEs) in Deli Serdang District by introducing and providing training on product innovation based on Thai cuisine. The main challenges faced by culinary MSME partners in the area include limited menu innovation, lack of awareness of current culinary market trends, and inadequate product packaging techniques. Additionally, these MSMEs struggle with mastering digital marketing strategies, which have become increasingly crucial in the post-pandemic era. To address these issues, the program employs a participatory approach involving training sessions, hands-on demonstrations, interactive discussions, and intensive mentoring. An experiential learning method is applied to ensure participants not only understand the concepts but are also able to implement them directly and effectively. Preliminary results indicate that 87% of participants experienced improved understanding of Thai menu innovation, while 76% successfully developed new product variations inspired by Thai recipes but adapted to local ingredients. Moreover, 65% showed improved skills in attractive product packaging, and 58% were able to promote their products through social media platforms as part of a digital marketing strategy. This approach has demonstrated a positive impact on enhancing the competitiveness of local culinary MSME products.